Wafer‐Scale Highly Ordered Anodic Aluminum Oxide by Soft Nanoimprinting Lithography for Optoelectronics Light Management. Issue 5 (27th January 2017) - Zhang, Chi; Li, Wenchao; Yu, Dongliang; Wang, Yanshan; Yin, Min; Wang, Hui; Song, Ye; Zhu, Xufei; Chang, Paichun; Chen, Xiaoyuan; Li, Dongdong
Abstract : The porous anodic aluminum oxide (AAO) membranes have been intensively studied as nanoscale templates for material fabrication. However, the preparation of large‐area highly ordered AAO remains a challenge. In this work, the large‐area soft polydimethylsiloxane mold is employed to transfer the nanopatterns onto Al foil substrates by UV nanoimprinting lithography. It is found that the anodizing behaviors are closely related to the electric field profiles, which can be defined by the morphologies of nanoindentations. The first‐step anodization carried out on the chemical etched patterns leads to some sub‐pores randomly distributed in the main channels. After removal of the as‐formed oxide layer, the stepwise second anodization produces highly ordered inverted nanocone AAO structure. In order to explore the potential application as high‐performance light management nanostructure, electromagnetic simulations are performed on thin‐film perovskite (CH3 NH3 PbI3 ) photodetectors using the inverted nanocone AAOs as a substrate. The results indicate that the nanotextured substrate delivers a much higher absorption property than the flat counterpart, demonstrating a promising application for high‐performance optoelectronic devices. Abstract : A scalable method to prepare highly ordered porous anodic aluminum oxide membranes is developed by transferring the nanoscaled patterns onto Al foil through full‐area soft nanoimprinting lithography. The porous membranes with tunable morphologies provide a versatile platform for high‐performance optoelectronic devices with feasible optical management strategy.